Pantun Users in The Classical Malay Era and Pantun in The Digital Era - Nur, Hidayatun; Asnawi, Asnawi; Mukhlis, Muhammad; Hermaliza, Hermaliza; Sukenti, Desi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
Pantun is important to study in the digital era because pantun is an intangible cultural heritage that needs to be preserved because it contains many values ​​and politeness in terms of language. Pantun is known to be widely used by people in the Classical Malay era which is said to be different from the use of pantun in the digital era where pantun is now rarely used by people. In reality, pantun in the digital era is widely used by people from various circles. This study aims to describe and explain the differences in users of Malay pantun in the Classical Malay era and pantun in the digital era. The form of this research is descriptive qualitative research using a phenomenological strategy. The data sources for this study are Classical Malay pantun collection books, pantun found on social media, pantun collection books in the digital era and from informants. Data collection techniques in this study are document studies, observations, questionnaires, and interviews. Data validation uses method triangulation techniques, theory triangulation and source triangulation. Data analysis uses interactive data analysis including data reduction, data presentation, drawing conclusions. The  results of the study concluded that there were differences in pantun users in the Classical Malay era and the digital era. The difference in terms of users is based on the use of pantun in various situations, namely persona users, pantun, chanters and storytellers. In addition, pantun, which was originally an oral tradition, has become digital content in the digital era.